Misericordiae vultus: Bula de S. S. Francisco. Sobre el Jubileo extraordinario de la Misericordia. (Ediciones UC, 2015)
On the occasion of the Year of Mercy, which will be celebrated during 2016, Pope Francis promulgated the bull Misericordiae Vultus (The Face of Mercy). The Pontifical Catholic University of Chile, through Ediciones UC, and the Episcopal Conference present this document as a new edition of their line of pontifical texts. In the text, the Holy Father not only suggests a detailed programmatic plan on how to live this time on a personal, local and global level, but also develops the Christian concept of mercy, explaining that it is like the love of a father or a mother that is they are deeply moved by their son (cf. MV 6).